Ecology and distribution of ground beetles in an isolated forest ecosystem of Medvednica Mountain. - Jelaska, Lucija Seric; Durbesic, Paula (Contributions to Entomology = Beiträge zur Entomologie, 2006)
The objective of the study was to determine the assemblage of carabids on the centre profile of Medvednica mountain, and their distribution in different forest communities according to various ecological factors: numbers of plant species, altitude, slope, aspect, soil acidity, canopy openness, leaf area index, flow accumulation potential, Pb, Cd, Zn, Cu, Ca concentrations and portion of soil organic matter. Ground beetles were sampled by pitfall traps on six plots that were vertically distributed, from bottom to top of the mountain on southern and northern slopes. For calculating biodiversity and habitat preferences according to available ecological factors, diversity indices were calculated, and RDA analyses was performed respectively. 43 species of carabids were recorded, with great differences in species richness and number of their specimens between plots. The greatest biodiversity was recorded for plot placed in Chrysanthemo macrophylli – Aceretum pseudoplatani forest community (according to Shannon-Wiener index = 3,7) and the lowest for plot placed in Luzulo – Fagetum sylvaticae (2,7) with the lowest pH and plant species diversity. Cluster analyses revealed differences in carabid assemblage between southern and northern slope of Medvednica. Some species like Carabus convexus, Notiophilus rufipes and Carabus intricatus were found exclusively on southern slope of mountain, in contrary to Carabus irregularis, Notiophilus biguttatus, Molops elatus, Platyderus rufus and all of the collected species of the genus Pterostichus recorded exclusively on northern parts of mountain. Among all analysed ecological factors, temperature, soil acidity and plant species richness had the greatest influence on spatial distribution of carabids across investigated area.